Prototype of REST Location-based Service for Trip Planning by Paratransit (Mikrolet) in Malang City - Kharisma, Agi Putra; Pinandito, Aryo (Journal of Information Technology and Computer Science, 2019)
Paratransit (mikrolet) was very popular in Malang city. However, their popularity is reduced by the availability of wide variety of more modern and online public transportations. One of the obstacles commonly faced by passengers of mikrolet is the limited information about the routes taken by mikrolet. In this paper, we proposed a prototype of service that can generate trip planning by mikrolet. We use depth-first search (DFS) algorithm as the basis to build our solution because it is relatively simple to modify. The service for trip planning available through REST web service and utilize location-based service style. Based on functionality testing result, the proposed system successfully generate all trip plans as expected. From performance perspective, when the number of routes and plans increased, the overall system performance degrades, so in the future the proposed prototype and its algorithm may needs further optimization.